(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2026)
The essence of the concept of political ideology, its role in the development of society, and the interpretation of ideology in the teachings of Eastern and Western thinkers are studied. A comparative analysis of the political doctrines of Eastern thinkers such as Abu Nasr Farabi, Amir Timur, Western scholars Destut de Tracy, Mannheim, Gramshi, Gouldner, Voloshinov on political ideology is carried out. In the course of the research, the role of ideology in the management of society, ensuring social stability, and the formation of state and civil relations is analyzed. The main goal of the research is to illuminate the theoretical foundations of the concept of political ideology, to reveal how the issue of ideology was interpreted in the views of Eastern and Western thinkers, and to analyze the influence of these views on modern political processes. The methodological basis of the research is historical-comparative analysis, a systematic approach, the logical-analytical method - a comparative study of the views of Eastern and Western thinkers, an analysis of the role of ideology in the political system as a whole, a logical interpretation of the concept of political ideology and its elements. The research results will serve as additional educational material for students studying political science, philosophy, history, and social sciences. Ideological aspects of the teachings of Eastern thinkers - although there are commonalities between Eastern and Western political thought, their ideological foundations differ significantly. In the East, politics is harmonized with spiritual and moral values, while in the West, emphasis is placed on the political system, law, and civil rights. At the same time, the common goal of both schools is the formation of a just society and ensuring the stability of society. Thus, by identifying the commonalities and differences in the views of Eastern and Western thinkers, it is possible to determine which ideas are of priority importance in modern political processes. It will also be possible to determine the influence of various political ideologies on public consciousness, their role in the formation of management systems, and their contribution to the development of political culture. Key words: idea, ideology, political ideology, western ideology, eastern ideology